Liquid-liquid Extraction of Copper(II) ions from Sulfate Media with Salicylidene Chloroaniline Isomers. Issue 2 (3rd March 2016) - Bouzgou, Mihad; Almi, Sana; Barkat, Djamel
Abstract: The liquid-liquid extraction of copper(II) ions from sulfate media with three Schiff bases extractants used were salicylidene-2-chloroaniline, sal-2-cla, salicylidene-3-chloroaniline, sal-3-cla, and salicylidene-4-chloroaniline, sal-4-cla, diluted in chloroform at 25°C are studied with the following parameters: pH and concentration of the extractant. The geometries of three extractants are optimized using DFT approximations at B3LYP/6-31G+ (d.P) bases set and the Gaussian 09 programs. Stoichiometry coefficients of the extracted species are determined by the slope analysis method. The copper(II) is extracted as a simple chelate CuL2 . The estimated extraction constants (log Kex ) relative to the three extractants reveal that the extraction efficiency increases in the order: sal-4-cla ∼ sal-3-cla > sal-2-cla.